2016
DOI: 10.1111/acer.12917
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Ethanol During Pregnancy and Lactation Affects Glutamatergic System and Induces Oxidative Stress in Offspring Hippocampus

Abstract: The decline in glucose transport coincided with increased lactate dehydrogenase activity, suggesting an adaptative response in EtOH-exposed offspring hippocampus, using lactate as an alternative fuel. These events were associated with oxidative damage, as demonstrated by changes in the enzymatic antioxidant defense system and lipid peroxidation. Taken together, the results demonstrate that maternal exposure to EtOH during pregnancy and lactation impairs glutamatergic transmission, as well as inducing oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Oxidative stress, which has been strongly implicated in congenital heart defect, is a potent apoptotic inducer (Wu et al 2016). In line with previous studies, as shown in the heart (Shirpoor et al 2015) and other tissues (Cesconetto et al 2016;Nogales et al 2017;Shirpoor et al 2014), we demonstrated that maternal ethanol exposure disrupted the oxidative balance in the myocardial tissue of the pups that was manifested by increasing the MDA and decreasing the TAC content.…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress, which has been strongly implicated in congenital heart defect, is a potent apoptotic inducer (Wu et al 2016). In line with previous studies, as shown in the heart (Shirpoor et al 2015) and other tissues (Cesconetto et al 2016;Nogales et al 2017;Shirpoor et al 2014), we demonstrated that maternal ethanol exposure disrupted the oxidative balance in the myocardial tissue of the pups that was manifested by increasing the MDA and decreasing the TAC content.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to previous studies using standard chow (29)(30)(31)(32) , maternal EtOH consumption during pregnancy decreased body (3.7% at PD3; 5.1% at PD7), brain (5.8%) and liver weights (5.7%) of pups born to dams fed chow, but these results did not reach statistical significance. In an earlier study, it was reported that maternal EtOH consumption from GD14 to GD19 significantly decreased body weight in fetuses but not in postnatal pups (33) .…”
Section: Effects Of Maternal Diet and Etoh On Birth Outcomessupporting
confidence: 79%
“…In our study, we also tried to explore the relationship between energy metabolism and the decrease in learning and memory ability of rats. LDH and SDH are two important energy metabolism enzymes that can reflect changes in cellular energy metabolism [36][37][38] . Our research found that combined exposure with 1.5 GHz and 4.3 GHz microwave radiation was able to cause a decrease in the activities of LDH and SDH in the hippocampal tissue of rats.…”
Section: Discussionmentioning
confidence: 99%